Effects of grape pomace on growth performance, serum biochemical indices, amino acid composition, and rumen microbial diversity in Dorper × Hu hybrid sheep - Sun, Xinchang; Zhang, Xia; Teng, Meimei; Li, Yuanqiu; Qi, Jiangjiao; Mamtimin, Tursunay; Wu, Wenda; Wan, Jiangchun (Frontiers in Veterinary Science, 2026)
IntroductionGrape pomace (GP), a byproduct of wine-making, is rich in nutrients and bioactive compounds. However, its effects on the health and rumen microbial diversity of fattening rams remain insufficiently studied. This study investigated the impact of dietary GP supplementation on Dorper × Hu hybrid sheep.MethodsEighteen male F1 Dorper× Hu hybrid sheep were randomly divided into three groups. They were fed complete pelleted diets containing 0% (control), 15%, or 20% GP for 60 days. Growth performance, serum biochemical indices, amino acid profiles in the longissimus dorsi muscle, and rumen bacterial composition were evaluated.ResultsThe key findings were: (1) GP inclusion did not negatively affect growth performance. (2) It significantly increased serum total protein levels and total antioxidant capacity, and elevated the content of essential amino acids in the muscle. (3) While overall rumen microbial diversity was not altered, GP supplementation specifically reduced the abundance of certain potentially harmful bacteria, such as Treponema.DiscussionThe results demonstrate that incorporating GP into the diet can enhance antioxidant status and improve muscle amino acid profiles in Dorper × Hu hybrid sheep, without compromising production performance. The selective reduction in specific rumen bacteria suggests a modulatory effect. This study provides a theoretical foundation for the effective utilization of GP in complete pellet feeds for ruminants.